On the specificity of bilingual language control: A study with Parkinson's disease patients. Issue 3 (8th May 2020) - Cattaneo, Gabriele; Costa, Albert; Gironell, Alexandre; Calabria, Marco
Abstract: This study investigates the relationship between mechanisms involved in language control within dual- and single-language contexts by examining whether they are similarly impaired in bilingual PD patients. To do so, we explored the performance of bilingual individuals affected by PD and healthy controls on two linguistic tasks: between-language and within-language switching tasks. We focused on switch and mixing costs as measures of linguistic control. The results indicate that, whereas larger switch costs were observed in PD patients, compared to controls, solely during the between-language task, larger mixing costs appeared during both the between-language task and the within-language task. These results are discussed within the framework of the dual mechanism hypothesis, which suggests that switch and mixing costs are measures of two types of control: specifically reactive and proactive control. Therefore, we conclude that reactive control for switching between languages is domain-specific while proactive control mechanisms are more domain-general.